The main principles of modelling the interaction between transport infrastructure development and economy - Jurkauskas, Algirdas; Micevičiene, Diana; Prunskiene, Jurgita (Transport, 2005)
The practical need of measuring the interaction between transport infrastructure development and economic growth is determined by the neccesity to justify huge invetsments in infrastructure projects. As it was established the actualify of the topic analysed is proved by many authors working in the field. However, the main shortcoming in the presented work (stress only on the relationship transport infrastructure – economy expressed in the terms of additional production of GDP) is the existence of the playback between the interdependent items. Considering the practice to be cardinally inadequate in the terms of economic theory and modern attitude to ecological problems,the authors of the article present the main principles of quantitive evaluation of the aforementioned realationship taking into account overlaping links of the categories analysed. First Published Online: 27 Oct 2010